Turning student assignments into publications: Benefits for librarians and students (Journal of EAHIL, 2022)
This article describes librarian involvement in a graduate student assignment to conduct rapid scoping reviews.  Students had the option to submit a manuscript for publication.  The librarian role through assignment conception to publication is detailed.  The benefits for both students and the librarian are discussed.